Raising to conformity without strictness: is it achievable? - Alcaide, Marta; Garcia, Oscar F.; Gomez-Ortiz, Olga; Garcia, Fernando (Frontiers in Psychology, 2025)
BackgroundThe prevailing belief that parental strictness is optimal for children is not uniformly supported by recent research. Contrary to the traditional notion that strictness is necessary to ensure children’s conformity to social norms, contemporary studies question its necessity. This study aims to analyze how two main parenting dimensions, warmth and strictness, are related to the psychosocial adjustment of children.MethodA sample of 1,224 Spanish adolescents and young adults was examined, divided into two groups: adolescents aged 12–18 years (51.14%) and young adults aged 19–35 years (48.86%). Adolescent participants were recruited from high schools while young adults were recruited from university courses. Children (i.e., adolescent and young adult offspring) responded to an online questionnaire that included all measures: parenting dimensions (warmth and strictness) and children’s psychosocial adjustment criteria (emotional self-concept, self-esteem, social competence, and conformity). Power analyses (a priori and sensitivity analyses) were applied to ensure sufficient sample sizes to achieve adequate power. Cohen’s d values from correlation analyses and multiple linear regression analyses were performed. Beta confidence intervals were analyzed to relate parenting dimensions, sex and age to self-concept, self-esteem, social competence, and conformity.ResultsThe statistical analysis plainly indicated that parental warmth was positively associated with criteria for child psychosocial adjustment, including self-esteem, social competence, and conformity. This relationship was consistent across both adolescents and young adults. Conversely, parental strictness was either negatively related to or not significantly associated with these criteria.ConclusionThis study clearly suggests that, completely contrary to expectations that strict parenting might be a need component to achieving psychosocial adjustment, parental warmth, rather than strictness, is more effective in promoting children’s psychosocial adjustment.